Best Proximity Points for Relatively -Continuous Mappings in Banach and Hyperconvex Spaces - Jack Markin; Naseer Shahzad (Abstract and Applied Analysis)
We prove some best proximity point results for relatively -continuous mappings in Banach and hyperconvex metric spaces. Our results generalize and extend some recent results to relatively -continuous mappings and to general spaces.